2008
DOI: 10.1016/j.cyto.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The expression of IL-20 and IL-24 and their shared receptors are increased in rheumatoid arthritis and spondyloarthropathy

Abstract: The purpose of this study was to analyze the expression of the two proinflammatory cytokines IL-20 and IL-24 and their shared receptors in rheumatoid arthritis and spondyloarthropathy. IL-20 was increased in plasma of rheumatoid arthritis patients compared with osteoarthritis patients and IL-24 was increased in synovial fluid and plasma of rheumatoid arthritis and spondyloarthropathy patients compared with osteoarthritis patients. IL-20 and IL-24 mRNA was only present at low levels in the synovium. In the syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 31 publications
7
75
2
2
Order By: Relevance
“…IL-24 is produced not only by activated immune cells but also to a similar extent by nonimmune cells such as cultured melanocytes (10), dermal keratinocytes (17), and IL-1-stimulated human colonic subepithelial myofibroblasts (18). IL-24 expression also has been reported in affected joints of rheumatoid arthritis patients (19) and is involved in the immunopathology of psoriasis (17,20) at the edge of excisional skin wounds (21) and in active lesions from patients who have ulcerative colitis and Crohn's disease (18). IL-24 inhibits differentiation of germinal center B cells into mature plasma cells and promotes their maturation toward the memory B cell pathway (22).…”
Section: P Roper Differentiation Of Naive Precursor T Cells Into Effementioning
confidence: 99%
“…IL-24 is produced not only by activated immune cells but also to a similar extent by nonimmune cells such as cultured melanocytes (10), dermal keratinocytes (17), and IL-1-stimulated human colonic subepithelial myofibroblasts (18). IL-24 expression also has been reported in affected joints of rheumatoid arthritis patients (19) and is involved in the immunopathology of psoriasis (17,20) at the edge of excisional skin wounds (21) and in active lesions from patients who have ulcerative colitis and Crohn's disease (18). IL-24 inhibits differentiation of germinal center B cells into mature plasma cells and promotes their maturation toward the memory B cell pathway (22).…”
Section: P Roper Differentiation Of Naive Precursor T Cells Into Effementioning
confidence: 99%
“…Binding of IL-20 to its corresponding complexes causes elevated proinflammatory activity in mesangial cells, keratinocytes, endothelial cells, synovial fibroblasts, and renal epithelial cells (Blumberg et al, 2001;Otkjaer et al, 2007). An inflammatory-promoting activity of IL-20 was found to be markedly associated with features of development and pathogenesis of various diseases and conditions (Hofmann et al, 2012), including those of rheumatoid arthritis (Hsu et al, 2006;Kragstrup et al, 2008;Hsu and Chang, 2010), atherosclerosis (Caligiuri et al, 2006;Chen et al, 2006;Kleemann et al, 2008), psoriasis (Wei et al, 2005;Sa et al, 2007;Wang et al, 2012b), brain injury (Chen and Chang, 2009), ulcerative colitis (Fonseca-Camarillo et al, 2013), and renal failure (Li et al, 2008a). In addition, IL-20 overexpression in transgenic mice resulted in neonatal lethality with skin abnormalities including aberrant epidermal differentiation (Blumberg et al, 2001).…”
Section: Interleukin-20mentioning
confidence: 96%
“…It has been demonstrated that the complement receptors CR1, CR3, and CR4 are up-regulated in RA neutrophils [17] simultaneously with enhanced peripheral degranulation, superoxide anion generation, and increased chemotaxis to synovium [18]. Neutrophil recruitment is promoted by TNF-a, IL-17, IL-20, and IL-24, all with impact on bone turnover [19,20]. Recently, Poubelle and co-workers reported that RA neutrophils express RANKL and are activated through RANK/RANKL interaction [21].…”
Section: Introductionmentioning
confidence: 99%